Delineating Novel Signature Patterns of Altered Gene Expression in Schizophrenia Using Gene Microarrays - Karoly Mirnics; Frank A. Middleton; David A. Lewis; Pat Levitt (The Scientific World Journal)
Schizophrenia is a complex and devastating brain disorder that affects 1% of the population and ranks as one of the most costly disorders to afflict humans. This disorder typically has its clinical onset in late adolescence or early adulthood, presenting as a constellation of delusions and hallucinations (positive symptoms); decreased motivation, emotional expression, and social interactions (negative symptoms); and impaired learning and memory (cognitive symptoms). The etiology of schizophrenia is unknown, but appears to be multifaceted, with genetic and epigenetic developmental factors all implicated. A convergence of observations from clinical, neuroimaging, and anatomical studies has implicated the dorsal prefrontal cortex as a major locus of alterations in schizophrenia.